Knowledge mobilization to spread awareness of the 'F‐words' in childhood disability: lessons from a family–researcher partnership. (10th April 2015) - Cross, A.; Rosenbaum, P.; Grahovac, D.; Kay, D.; Gorter, J. W.
Abstract: Background: In 2012, two CanChild researchers published an article in C hild: C are, H ealth and D evelopment titled 'The "F‐words" in childhood disability: I swear this is how we should think!' Building on the World Health Organization's International Classification of Functioning, Disability and Health (ICF) framework, the article featured key strengths‐based ICF themes (i.e. the 'F‐words' – Function, Family, Fitness, Fun, Friends and Future). This paper reports on a knowledge mobilization initiative designed to spread awareness of the 'F‐words' ideas. Methods: Families and researchers collaborated to develop, disseminate and evaluate an online awareness video. The video used written descriptions, parents' reflections and their pictures, music and graphics to captivate the audience. Posted on the CanChild website in May 2014, information about the video was distributed via various dissemination strategies and evaluated by tracking its views and through an online survey. Results: After a 2‐month evaluation, there were 715 views and 137 survey responses. Of the survey responses, 89% lived in Canada, 55% had not previously heard of the 'F‐words', 98% 'extremely liked'/'liked the ideas' and 88% indicated they would share the video. Conclusions: By creating a short and captivating video, we were able to spread awareness to a wide audience in a short period of time. Engaging families throughout the project was critical to the success of the video. By working together, we hope to continue bridging research and practice and moving the 'F‐words' concepts forward one 'word' at a time.